Una nueva “comadreja” (Mammalia, Marsupialia, ?Polydolopimorphia) del Paleoceno de Patagonia, Argentina - Goin, Francisco Javier (1998)
Upper and lower molars belonging to Palangania brandmayri n. gen. et sp., a new ?polydolopimorphian marsupial of late Paleocene (Riochican) age are described. All specimens belonging to this new taxon were recovered from levels referable to the Koluel-Kaike Formation (Rio Chico Group) at Pico Salamanca (Chubut Province, Argentina). The bunodont molars with inflated cusps and wide protocones and talonids suggest that Palangania brandmayri had omnivorous or omnivorous-frugivorus feeding habits. The lower molars bear low protoconids; the metaconids (especially that of the first molar) are located slightly posterior to the protoconids. The para- and metaconids are subequal in height and linked by a crest. The talonid basins are shallow, and vestigial hypoconulids occupy an almost central position on the posterior edge of the talonid. Upper molars have large, wide protocones, small pre- and postprotoconular cinguli, and relatively large metaconules. The paraconules are vestigial or absent. The postpostmetacrista of the third molar is subequal to, or slightly shorter than, that of the second molar. The apex of the weakly developed, “U”-shaped centrocristae lies close to the labial margin. Stylar cusps B and D are large, the former being much larger than the paracone. A smaller cusp C is present on the third molar, but absent from the second. Para- and metacones are located close to stylar cusps B and D, respectively. It is difficult to assess the relationships of Palangania. The incipient twinning of cusps B and D with the para- and metacone, as well as the larger size of the metaconule with respect to the paraconule, suggest polydolopimorphian affinities. In contrast, the lower molars share several derived features with microbiotheriids, such as Pachybiotlieriuin or Eomicrobiotherium, viz. low cusps, hypoconulid reduced and medially placed on the posterior edge, small paraconid, and vestigial anterobasal cingulum. Alternately, the moderate enlargement of cusps B and D, small size of the last molar, weak centrocrista, preparacrista connecting with cusp A, and the relatively narrow stylar shelf suggest Glasbiinae affinities. (The last two features are also shared with microbiotheriids). Several of the latter features are strongly expressed in Polydolopimorphians; therefore, a phylogenetic hypothesis that considers microbiotheriids (including glasbiines), Palangania. and Polydolopimorphia as a monophyletic group is given preliminary consideration.